Biotechnology An Introduction - Barnum, Susan R (Thomson Brooks/Cole, 2005)
Gives a solid understanding of the key concepts and issues in the rapidly expanding field of biotechnology then goes on to describe the processes and methods used to manipulate living organisms, and the substances and products from them, for medical, agricultural and industrial purposes.